Daptomycin and vancomycin non-susceptible methicillin-resistant Staphylococcus aureus clonal lineages from bloodstream infection in a Brazilian teaching hospital - Andreia Paredes Damasco; Thaina Miranda da Costa; Priscylla Guimarães Migueres Morgado; Lorrayne Cardoso Guimarães; Fernanda Sampaio Cavalcante; Simone Aranha Nouér; Kátia Regina Netto dos Santos (Brazilian Journal of Infectious Diseases, 2019)
Introduction: This study aimed to characterize Staphylococcus aureus isolates from bloodstream infections in patients attending a teaching hospital, between 2011 and 2015. Methods: The minimum inhibitory concentration for daptomycin, linezolid, oxacillin, teicoplanin, vancomycin, and trimethoprim/sulfamethoxazole was accessed by broth microdilution. SCCmec type and clonal profile were determined by molecular tests. Vancomycin heteroresistance was evaluated using screening tests and by population analysis profile/area under the curve. Results: Among 200 S. aureus isolates, 55 (27.5%) were MRSA, carrying SCCmec II (45.5%) or IV (54.5%). The most frequent MRSA lineages were USA100 (ST5-II) (45.5%) and USA800 (ST5-IV) (30.9%). Six isolates were confirmed as vancomycin heteroresistant, showing area under the curve ratio 1.1, 1.2 or 1.3 (four USA100, one USA800 and one USA1100 isolates). Conclusions: Daptomycin and vancomycin non-susceptible MRSA clonal lineages were found in bloodstream infections over five years, highlighting the importance of continuous surveillance of multiresistant bacteria in hospitals. Keywords: Bloodstream infection, S. aureus, Vancomycin, Daptomycin